PENGARUH KOMBINASI PROGRESSIVE MUSCLE RELAXATION (PMR) DENGAN MUSIK INSTRUMENTAL ISLAMI TERHADAP KUALITAS TIDUR PADA IBU HAMIL TRIMESTER III TAHUN 2023 - Anis Partiwi (2023)
Pregnancy experiences change both psychologically and physiologically. These changes cause discomfort which will generally have an impact on decreasing the quality of sleep, especially in third trimester pregnant women. Several studies have shown that poor sleep quality can have a negative impact on both the mother and fetus. The purpose of this study is to determine the effect of Progressive Muscle Relaxation (PMR) with islamic instrumental music combination on sleep quality of third trimester pregnant women. The design of this study is a quasi-experiment in the form of a non-randomized pretest and posttest control group which was analyzed by paired t-test and independent t-test. The number of samples is 42 third trimester pregnant women with the sampling technique using consecutive sampling. The experimental group was given intervention for 10-15 minutes every night for 3 consecutive days. While the control group was not given any intervention. The instrument for assessing sleep quality uses the Pittsburgh Sleep Quality Index (PSQI). The results of the study obtained a p value of 0.000 <0.05 which can be concluded that there is an effect of giving Progressive Muscle Relaxation (PMR) with islamic instrumental music combination on sleep quality of third trimester pregnant women. In this study, it is hoped that third trimester pregnant women can apply this therapy to help improve sleep quality.